Management of whiplash-associated disorder in the Italian emergency department: the feasibility of an evidence-based continuous professional development course provided by physiotherapists. Issue 10 (8th May 2022) - Mourad, Firas; Patuzzo, Alberto; Tenci, Andrea; Turcato, Gianni; Faletra, Agostino; Valdifiori, Gianluca; Gobbo, Massimiliano; Maselli, Filippo; Milano, Giuseppe
Abstract: Purpose: The management of whiplash and associated disorders (WAD) in the Italian Health System is still empirical and influenced by a single professional's expertise. Therefore, the purpose of our study is to describe a structured management changes in an Italian emergency department (ED) after an evidence based continuous professional development (CPD) course. Methods: A CPD course was organized by Orthopedic Manipulative Physical Therapists (OMPT) for personnel of ED in the hospital Girolamo Fracastoro (San Bonifacio, Verona, Italy), based on latest scientific evidence. Data regarding the number of X-Rays, computed tomography (CT) scan, orthopaedic referrals, neck collars and WAD IV (i.e., severe diagnosis) before and after the course were compared. Results: 3066 cases of WAD have been analyzed in 2016 and 2185 in 2017/2018. The number of X-Rays dropped down from 15.1% to 13.5%; the CT scans increased from 1.3% to 1.9%; the WAD IV diagnosis increased from 0.7% to 1.6%; the orthopaedic referrals dropped from 1.5% to 1.1%; the collars prescription dropped from 8.8% to 2.5%. Conclusion: An updated framework increased the efficiency of ED's maintaining the same level of safety (i.e., WAD IV diagnosis). Given that, it can also be argued that, in line with other countries, the implementation of an OMPT role within the ED multidisciplinary team is advised also in Italy. Implications for rehabilitation: Physiotherapists were commissioned to organize a management change of patients in an Italian Emergency Department clinical setting for the management of whiplash; Guidelines and other appropriate clinical rules facilitate the delivery of an evidence-based and more appropriate management and care plan; An inter-disciplinary continuous professional development course has the potential to positively influence patients' journey and to optimize the use of departmental resources; The involvement of other health professionals (e.g., Physiotherapists) within the Italian Emergency Department organizational chart might lead to further improvement of service provided.